Histological examination in sudden unexpected death in infancy: evidence base for histological sampling. Issue 1 (30th September 2011) - Weber, M A; Pryce, J W; Ashworth, M T; Malone, M; Sebire, N J
Abstract : Aim: Pathologists currently follow the 'Kennedy guidelines' when performing autopsies for sudden unexpected death in infancy (SUDI); these include extensive histological sampling. This study establishes the frequency with which histological examination of visceral organs determines cause of death and examines associations between clinical, macroscopic and microscopic findings. Methods: Retrospective review of 546 SUDI autopsies performed for a 10-year period (1996–2005) at a single centre. The proportion of cases in which non-neuropathological histological examination directly determined the cause of death was identified, and clinical, macroscopic and histological findings at autopsy were compared. Results: Of 510 SUDIs included, 166 cases were explained SUDI, and of these, 54% (89/166) were identified solely on microscopic examination, based on histology of the lungs in 71 (43%), heart in 13 (8%), liver in 4 (2%) and kidneys in 1 (<1%). The proportions of macroscopically normal organs with significant histological findings were 26% lungs, 2% heart and 1% each of liver and kidneys, but none of spleen, thymus, pancreas or adrenals. Macroscopically abnormal organs were more likely to yield significant histological features. Symptoms preceding death were more common in cases with significant histological findings in lungs, heart, liver and adrenals. Conclusion: A non-neuropathological cause of death in explained SUDI can be established from histological examination of lungs, heart, liver and kidneys. Significant histological abnormalities may be detected in selected organs with macroscopically normal appearances. Routine histological sampling of other organs in the absence of specific clinical history or macroscopic abnormalities has a low yield for establishing cause of death.